ACCURACY OF GLASGOW COMA SCALE (GCS) COMPONENTS AS PREDICTORS OF MORTALITY OF MODERATE AND SEVERE HEAD INJURY CLIENTS - Riki Ristanto (UNEJ e-Proceeding, 2023)
In moderate and severe head injury clients with multiple traumas, there may be difficulty calculating GCS scores due to facial trauma to the eyes and mouth. This condition makes it difficult for nurses and emergency room doctors to calculate client prognosis using GCS. This study aims to analyze the ability of GCS components as a predictor of mortality for moderate and severe head injury clients. This study is an observational study with a retrospective cohort design. The population is the medical record data of head injury patients admitted in the period January to December 2020 at Dr. Iskak Tulungagung Hospital. A sample of 115 medical records was obtained through purposive sampling method. The variables were GCS score in emergency department triage data and mortality data of head injury clients within seven days of treatment. The results were analyzed by Mann Whitney Test, logistic regression and ROC Curve comparison. The logistic regression result of GCS score has sensitivity = 0.904, specificity = 0.809, PPV = 0.955, NPV = 0.654; GCS-Eyes has sensitivity = 0.938, specificity = 0.617, PPV = 0.854, NPV = 0.807; GCS-Verbal has a sensitivity = 0.929, specificity = 0.667, PPV = 0.887, NPV = 0.769; GCS-Motor has a sensitivity = 0.833, specificity = 0.692, PPV = 0.955, NPV = 0.346. ROC Curve comparison results show ROC GCS = 0.952, GCS-Eyes = 0.870, GCS-Verbal = 0.885, GCS-Motor = 0.903. The conclusion is that the GCS-Motoric component is the GCS component that has the best accuracy after GCS. Keywords: Head Injury, GCS Components, Mortality Prognosis.